Diagnosing microbiologically influenced corrosion at a crude oil pipeline facility leak site – A multiple lines of evidence approach. (August 2022) - Sharma, Mohita; Liu, Hongwei; Tsesmetzis, Nicolas; Handy, Joshua; Place, Trevor; Gieg, Lisa M.
Abstract: In crude oil transmission pipelines, some parts of the system receive minimal or no fluid flow ('dead legs'), which can on occasion lead to under deposit corrosion wherein a mixture of sediments, hydrocarbons, water, and microorganisms collectively contribute to an integrity failure. However, the microbial contribution to this phenomenon in crude oil transmission pipelines is poorly characterized. To better understand this process, we used a multiple lines of evidence approach to examine a dead leg failure event using sludge samples collected from at andnear the leak location and from non-corroded areas on the same pipe segment. Chemical analyses revealed elevated levels of acetate, total iron, and FeCO3 at the leak locations compared to non-corroded areas. Electrochemical techniques showed increased evidence for corrosion in leak site samples compared to non-corroded samples, while corrosion coupon analysis revealed many localized pits of up to 20 μm deep in leak location samples compared to fewer pits that were up to 4 μm deep from the non-corroded sample after incubating the samples for 30 days. 16S rRNA gene analysis revealed sulfide-producers, acetogens, and methanogens in all collected samples. The lack of detection of FeS as a corrosion product, no significant differences in sulfate and sulfide concentrations across all samples, and elevated levels of acetate at the leak location suggested that acetogens and/or fermentative bacteria contributed to this pipeline leak. This study highlights the use of a multiple lines of evidence approach that can be used to garner evidence to determine the contribution of MIC to failures in dead leg pipeline segments. Highlights: Microbial corrosion is investigated at a dead leg pipeline failure location. (Electro)chemical, corrosion, and molecular microbiology tools are used. Increased corrosivity and chemical differences found at leak versus non-leak sites. Potentially corrosive microorganisms like acetogens are abundant at the site. A multiple lines of evidence approach is recommended for failure analysis.